Desenvolvimento de material de isolamento térmico compósito à base de sabugo de milho - Rosa, Fábio Severo da (2019)
One of the most important challenges for the construction industry is the reduction of environmental impacts at all stages of the life cycle. Among the possible guidelines for reducing environmental impacts is the use of recycled materials, whether in the civil construction sector or in other productive sectors, such as agriculture. Many researchers have focused their efforts on studying the potential of applying organic materials to construction. Among the organic matter, maize is produced mainly for animal feed. The grain enables the production of a series of industrialized products. However, some parts of the plant do not have a direct use, like corn cob. The objective of the research was to develop a composite with thermal insulation characteristics based on the corn residue of corn husks for use in construction. Three composites with different grades denominated (A, B, C) were developed and the thermal conductivity, bulk density and flexion were analyzed in three points. The composite B was the one that presented better mechanical resistance, being this chosen and submitted to the test of Thermogravimetry. This showed that the composite can be used in hot systems that are subjected to temperatures of up to 240 oC. All composites presented low conductivity and adequate density compatible with other composites based on lignocellulosic materials. The insulating properties of composite made and combined with elements already commonly used in vertical fence systems have been verified by means of calculations. The developed composite has demonstrated that the use of an agricultural residue for preparing thermal insulation material is possible.